2019
DOI: 10.1186/s13030-019-0168-x
|View full text |Cite
|
Sign up to set email alerts
|

The longitudinal effects of seated isometric yoga on blood biomarkers, autonomic functions, and psychological parameters of patients with chronic fatigue syndrome: a pilot study

Abstract: BackgroundIn a previous randomized controlled trial, we found that practicing seated isometric yoga regularly for 2 months improved the fatigue of patients with chronic fatigue syndrome (CFS) who are resistant to conventional therapy. The aim of this pilot study was to investigate the possible mechanisms behind this finding by comparing blood biomarkers, autonomic nervous function, and psychological indices before versus after an intervention period of seated isometric yoga practice.MethodsFifteen patients wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 72 publications
(121 reference statements)
0
10
0
Order By: Relevance
“…We demonstrated that regular practice of recumbent isometric yoga reduced the CFQ 11 scores of patients with ME/CFS. Several studies have already suggested the beneficial effects of yoga, although the type of yoga was different from that used in our studies, in at least a subset of patients with ME/CFS [46, 19] [46]. In a case report of one patient with CFS, yoga-based lifestyle intervention improved their clinical profile, positive aspects of personality, and subjective well-being, in addition to reducing anxiety [4].…”
Section: Discussionmentioning
confidence: 85%
“…We demonstrated that regular practice of recumbent isometric yoga reduced the CFQ 11 scores of patients with ME/CFS. Several studies have already suggested the beneficial effects of yoga, although the type of yoga was different from that used in our studies, in at least a subset of patients with ME/CFS [46, 19] [46]. In a case report of one patient with CFS, yoga-based lifestyle intervention improved their clinical profile, positive aspects of personality, and subjective well-being, in addition to reducing anxiety [4].…”
Section: Discussionmentioning
confidence: 85%
“…Eight studies measured anxiety and depression using the Hospital Anxiety and Depression Scale (HADS) [ 29 , 30 , 40 , 41 , 43 , 44 , 51 , 91 ]. Six studies measured quality of life or physical and/or mental functioning using different quality of life outcome measures [ 28 , 29 , 30 , 41 , 45 , 51 ].…”
Section: Resultsmentioning
confidence: 99%
“…Six studies measured quality of life or physical and/or mental functioning using different quality of life outcome measures [ 28 , 29 , 30 , 41 , 45 , 51 ]. Seven studies measured objective outcomes including ventilatory parameters [ 38 ], performance testing by computer programs [ 51 ], telomerase activity [ 70 ], autonomic nervous system functions, blood biomarkers [ 42 , 91 ], adiponectin levels [ 83 ], and microRNA changes [ 10 ]. Table 2 describes the details of these outcome measures and the other outcomes measured in the included studies.…”
Section: Resultsmentioning
confidence: 99%
“…As described earlier, these types of yoga programs would enable participants to obtain post-isometric relaxation and to enhance self-awareness, which may help them nd methods for coping with their stress. Furthermore, this style enables [28] people with debilitating diseases to participate in and reap the bene ts of yoga [9][10][11][12][13]. Due to these characteristics, the classes in the present study were more therapeutic rather than being designed to improve physical tness or personal appearance.…”
Section: Limitationsmentioning
confidence: 99%
“…A considerable number of studies have demonstrated that yoga has health-related bene ts in healthy individuals such as reductions of negative affect, perceived stress, and subjective somatic symptoms, as well as improvement in health-related quality of life [1][2][3]. Furthermore, cumulative studies have suggested that yoga also has bene cial effects for patients with stress-related diseases such as depressive disorders [4,5] and those with chronic illnesses such as breast cancer [6][7][8] and myalgic encephalomyelitis/chronic fatigue syndrome [9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%